Guided coronally advanced flap to treat gingival recession: Digital workflow and case report - Santamaria, Mauro Pedrine [UNESP]; Rossato, Amanda [UNESP]; Miguel, Manuela Maria Viana [UNESP]; Mathias-Santamaria, Ingrid Fernandes; Nunes, Marcelo Pereira; Queiroz, Lucas Araújo (Wiley, 2025)
BACKGROUND: The inherently technique-sensitive nature of periodontal plastic procedures demands a significant level of skill and expertise. The incorporation of three-dimensional (3D) printing technologies emerges as a potential strategy to optimize and simplify surgical procedures. This case report describes the digital workflow and presents the clinical outcomes achieved using a guided coronally advanced flap for the treatment of a single gingival recession (GR). METHODS AND RESULTS: A female patient with a gingival recession type 1 (RT1 B-) defect on the mandibular second left premolar underwent successful treatment using a guided coronally advanced flap (g-CAF) and de-epithelized connective tissue graft (CTG). The digital planning included intraoral scanning of the mandible and hard palate using an intraoral scanner, with resulting polygon format (PLY) files exported for virtual model creation. The CAF guide was meticulously designed to orient horizontal and vertical incisions at the papillae base adjacent to the GR defect. For the donor site, a guide was specifically created, positioning the graft area 2 mm apically to the premolars' gingival margins. The delineation of this area involved two horizontal and vertical incisions, meticulously based on the dimensions of the GR. The digitally designed guides were then 3D-printed using a surgical guide-specific resin, contributing to the precise execution of the innovative surgical approach. Complete root coverage was achieved. CONCLUSION: This case report demonstrates that g-CAF can be a promising approach for the treatment of single GR. HIGHLIGHTS: Why is this case new information? To the best of the authors' knowledge, this is the first manuscript to report a guided procedure for the treatment of gingival recession. This report provides the digital workflow for the fabrication of a guide to perform the coronally advanced flap for single recession defects. What are the keys to successfully manage this case? It is necessary to adequately scan the recession defect area and palate. Properly not only design the guide using specific software but also print it. The guide has to be stable when in position for the surgical procedure. What are the primary limitations of this technique? This guide was designed to help surgeons during the incisions. However, it does not provide aid to split and release the flap and suture.
Keywords: computer‐aided design; dental cervix autografts; dental esthetics; dentin sensitivity; gingival recession